Pembelajaran Penyelenggaraan Jenazah Dengan Dadar Berpajero Pada Mata Pelajaran Pedidikan Agama Islam (PAI) Di SMAN 1 Jombang - Mukani, Mukani (MADINAH, 2018)
Organizing the corpse into an even-grade semester XI PAI material, including bathing, memorizing, praying and burying. With this material, students are expected to be able to explain, demonstrate and apply the procedures for organizing bodies in their daily lives. But the facts in the field show that the learning method is still dominated by lectures and question and answer. This fact makes students easily bored while studying in class. This paper is the best practice experienced by the author when delivering material for organizing the corpse at SMAN 1 Jombang in the academic year 2017/2018 even in the XI-IPS-3 class. Dadar Berpajero stands for Demonstration, Learning to Care for People's Bodies. At first, PAI learning in the XI-IPS-3 class was dominated by lectures and question and answer. At the next meeting the demonstration method was used. Changes in this learning strategy provide significant results. Through Dadar Berbajero, teachers are easier to provide learning material. The learning atmosphere becomes more interesting and fun to be the main attraction for students to take part in the learning process until it's finished. The use of Dadar Berbajero on PAI has impacted the enthusiasm of students and their learning outcomes are also above the KKM. Positive responses were also given by the school community, starting with the principal, the board of teachers, employees and students